Hubungan Pengetahuan Gizi Ibu Dengan Waktu Pemberian MP-ASI Pada Bayi Di Wilayah Kerja PuskesmasTambun Selatan Kabupaten Bekasi - Alfiyah Mumtazah Firmansyah; Guntari Prasetya (Peneliti.net, 2023)
Based on data from the World Health Organization (WHO) it is stated that only 40% of infants in the world are exclusively breastfed, while 60% of other infants have been given complementary feeding under 6 months of age. Malnutrition can occur when complementary feeding of breast milk is not in accordance with the stages of age, quantity and quality. The results of a preliminary study that has been carried out in the Work Area of ​​the Tambun Selatan Health Center Bekasi on 10 mothers who have babies through interviews obtained the results of 20% of mothers with good knowledge, 40% with sufficient knowledge and 40% with less knowledge about nutrition knowledge and timing of complementary feeding on baby. This study was to determine the relationship between maternal nutritional knowledge and the timing of complementary feeding to infants in the Tambun Selatan Community Health Center, Bekasi Regency. This study is an analytical study with a cross-sectional design. The research subjects were all mothers who had babies aged 6-12 months. Data were collected using a questionnaire, data on the level of knowledge of maternal nutrition and the timing of complementary feeding were analyzed using chi square analysis. The results showed that there was a significant relationship between maternal nutritional knowledge and the timing of giving complementary feeding to infants in the South Tambun Health Center area of ​​Bekasi Regency (p-value = 0,0001). The conclusion of this study is that there was a significant relationship between maternal nutritional knowledge and the timing of providing the complementary feeding for infants.